Renovation of the faculty office in the Child Development Center U.P College of Home Economics a design proposal - Jabile, Joy Gladys J.
This research covered the evaluation of the CDC faculty office and the proposal of a new design. It sought to demonstrate a step-by-step and methodological process of coming up with a good working environment. The discussions of human importance of adequate lighting, acoustics, and privacy were also touched in these study. This research meant to propose changes to make the CDC office into a more spacious, more stimulating, and provide it with a comfortable office environment.